ON THE INFLUENCE OF THE ANTIQUE CULTURE ON THE CULTURE OF UKRAINE - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the author analyzes the peculiarities of the antique culture influence on the culture of Ukraine starting with the ancient world and up to the Renaissance period. A considerable role of the antique culture in the development of the national Ukrainian culture and preservation of its uniqueness is emphasized.